2018
DOI: 10.1186/s12875-018-0838-y
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of professional stakeholders’ perceptions about the implementation of a stepped care pain platform for people experiencing chronic widespread pain

Abstract: BackgroundChronic widespread pain (CWP) is a major public health problem. Many people experiencing CWP experience mental health problems such as anxiety or depression. Complete relief of skeletal and body pain symptoms is unlikely but with appropriate treatment the impact upon quality of life, functioning and mental health symptoms can be reduced. Cognitive behavioural therapy (CBT) is widely used for a range of health conditions and can have short and long-term improvements in patients with CWP. This research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It could be argued that a highly specialised healthcare service such as a pain centre, should contribute to a patient’s pain treatment only for a short period, transferring the follow-up responsibility to primary care and a GP; however, dissatisfaction with the quality of pain treatment in primary care, including GPs, has been reported [36] along with challenges with continuity of care throughout the health care systems for this group of patients [37]. In addition, it has been stated that it is vital that primary care practitioners have access to timely and appropriate multidisciplinary resources to support the health and well-being of their patients [38]. Consequently, it could be argued that pain centres, with their multidisciplinary teams, should be a service available to patients and their day-to-day providers at irregular intervals over time to optimise the efforts they initiate.…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that a highly specialised healthcare service such as a pain centre, should contribute to a patient’s pain treatment only for a short period, transferring the follow-up responsibility to primary care and a GP; however, dissatisfaction with the quality of pain treatment in primary care, including GPs, has been reported [36] along with challenges with continuity of care throughout the health care systems for this group of patients [37]. In addition, it has been stated that it is vital that primary care practitioners have access to timely and appropriate multidisciplinary resources to support the health and well-being of their patients [38]. Consequently, it could be argued that pain centres, with their multidisciplinary teams, should be a service available to patients and their day-to-day providers at irregular intervals over time to optimise the efforts they initiate.…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals with experiencing insomnia anxiety at the time approaching sleep because afraid no can sleep and the consequences that will be they natural during the day the day. Enhancement worry this can increase arousal when the arousal state should be decreased, so finally lower opportunity for sleep, and so it happened anxiety insomnia cycle (29). Opinion the supported by the research of (30) who found exists enhancement anxiety 2 -fold in individuals with insomnia compared sleeping individual.…”
Section: Connection Worry With Quality Sleepmentioning
confidence: 94%
“…A prospective cross-sectional qualitative exploratory study was conducted through focus group discussions (FGDs) and in-depth interviews (IDIs). Qualitative exploration from the perspectives of diverse stakeholders is considered the most useful approach when there is a high level of uncertainty about the study subject, as was the case with barriers toward optimal breastfeeding practices in Armenia (Gellatly et al, 2018). The study described in this article was part of a larger study concentrating on maternal and child nutrition at various stages (pre-pregnancy, during pregnancy, and post pregnancy).…”
Section: Methodsmentioning
confidence: 99%